Invariant Geometric Objects of the Canonical Almost-Geodesic Mapping π2 (e = 0) - Grigoreva, T. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For the canonical almost-geodesic mapping π2 (e = 0), we prove an analog of the Beltrami theorem in the theory of geodesic mappings. We introduce canonical π2-flat spaces and obtain metrics for them in a special coordinate system.